Торговля и торговые пути между Северной Сирией и Анатолией (4000-1500 гг. до н.э.) - Меллаарт, Дж.
Mellaart, J., Archaeological evidence for trade and trade routes between Syria, Mesopotamia and Anatolia, during the Early and the beginning of the Middle Bronze age (4000-1500 B.C.).